Paradigma Pembelajaran Sosial Konstruktivistik Zaid Sulaiman Al-Udwan Dalam Al-Naẓariyah Al-Bināiyah Al-Ijtimāiyah Wa Tathbiqātihā Fǐ Al-Tadrǐs - Zaitunah; Yanto, Yusri (LP2M Universitas Islam Ahmad Dahlan, 2023)
In the social learning educators and students must be required to be active in all learning activities by seeking learning activity through the practice of working on it, not enough through reading activity only. The process of learning with such a model, came to be known social constructivistic learning. The author is interested in reviewing further the learning paradigm in particular the paradigm of exploring social constructivism in the Zaid Sulaiman al-'Udwan’s book. This study found that the basic concepts of social constructivism, al-'Udwan relied on Vygotsky's theory of social constructivism, a process in which students' internal knowledge is modified in response to social and personal interactions. And the concept develops from the concept of al-Lughah, Al-Biah al-Ijtima 'iyah, Tafawudiyah, and Hayz al-Numuw al-Mumkin. Whereas the principles of the theory of social constructivism are learning to rely on individual and group methods, Focus on building concepts and meanings through social processes, learning is based on organizational methods, the negotiation process is the basis for generalizing, principled social constructivism. And the role of educators is encouraging independence and accepting students' initiatives and motivating students to be active in conducting discussions with educators and between students.